The effects of coal dust exposure on DNA damage and repair of human bronchial epithelial cells. (July 2022) - Li, Amin; Zhang, Yinci; Ma, Yongfang; Xu, Ruyue; Song, Li; Cao, Weiya; Tang, Xiaolong
To explore the effects of coal dust exposure on DNA damage and repair, human bronchial epithelial BEAS-2B cells were exposed to coal dust and the cellular response was investigated. It was found that γ-H2AX foci of DNA damage appeared, γ-H2AX protein level increased, and the rate of cell apoptosis was significantly elevated when BEAS-2B cells were exposed to coal dust for a short time. Phagocytized coal dust particles, swollen mitochondria, and reduced mitochondrial membrane potential were simultaneously identified. Moreover, Caspase-9, Caspase-3, and DFF45 proteins of the mitochondrial apoptotic pathway were activated. After the cells were exposed to coal dust chronically, phosphorylation levels of DNA repair kinases (ATM/ATR, DNA-PKcs) and downstream regulatory protein AKT were significantly upregulated. γ-H2AX foci and tail DNA of the cells following treatment with cisplatin were also reduced, and the colony formation rate was improved. It was concluded that coal dust could induce DNA damage, cause mitochondrial depolarization, and activate mitochondrial apoptosis pathways in BEAS-2B cells. Additionally, activated DNA repair kinases (ATM/ATR and DNA-PKcs) and their regulatory protein AKT increased DNA repair and proliferation of BEAS-2B cells chronically exposed to coal dust.